Short enantioselective synthesis of (-)-chloramphenicol and (+)-thiamphenicol using tethered aminohydroxylation - George, Shyla; Narina, Srinivasarao V.; Sudalai, Arumugarn (Tetrahedron, 2006)
An efficient enantioselective synthesis of (-)-chloramphenicol (1) and (+)-thiamphenicol (2) is described. These antibiotics have been synthesized from commercially available 4-nitrobenzaldehyde and 4-(methylthio)benzaldehyde, respectively, using tethered amino-hydroxylation and Sharpless asymmetric epoxidation as the chirality inducing steps. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: asymmetric epoxidation; Asymmetric synthesis; Kinetic resolution; Tethered aminohydroxylation